Kajian Distribusi Spasial Dan Temporar Kadar BOD, TSS dan Oksigen Terlarut (DO) Air Sungai Batang Harau Kota Padang - Burhan Muslim; Sejati Sejati; Awalia Gusti; Evino Sugriarta (Jurnal Kesehatan Lingkungan, 2020)
Biological Oxygen Demand (BOD), Total Suspended Solid (TSS), and Dissolved Oxygen (DO) are indicators of water quality in water bodies. Non-polluted water has low BOD and TSS levels and high DO. Changes in these three parameters indicate a change in quality. This study aims to look at variations in the levels of BOD, TSS, and DO spatially and temporarily in Batang Arau River, Padang City in 2018. The study was conducted by observing three stations, namely in the upstream, middle, and downstream, and in the morning and evening. The results showed that BOD and TSS levels tended to increase from upstream to downstream, while DO was the opposite. The temporal variation shows that BOD and TSS levels are low in the morning and increase during the day and evening, while DO is the opposite.